International relations in Southeast Asia between bilateralism and multilateralism - Ganesan, N. (Narayanan) 1954-; Amer, Ramses (Institute of Southeast Asian Studies, 2010)
"The central theme of this book is the utility of bilateralism and multilateralism in Southeast Asia international relations. The intention was to examine a sufficient number of empirical cases in the Southeast Asian region since the mid-1970's so as to establish a pattern of interactions informing a wider audience of interactions unique to the region. Through these case studies, we seek to identify how this pattern of interaction compares with similar experiences elsewhere vis-a-vis the theoretical underpinnings of multilateralism and bilateralism. Consequently, this book also examines the theoretical drift in international relations literature at the broadest level and the overall drift of Southeast Asian international relations between the nations themselves and the Association of Southeast Asian Nations (ASEAN)."